2018
DOI: 10.22491/rca.2018.2815
|View full text |Cite
|
Sign up to set email alerts
|

Densidade populacional de pentatomídeos influenciada pela estrutura morfológica de diferentes plantas no município de Cruz Alta, RS

Abstract: Contribuição dos autores: Eduardo Engel realizou o experimento, a análise de dados, a revisão bibliográfica, a escrita científica e a apresentação dos resultados; Maurício Paulo Batistella Pasini contribuiu com a escrita científica, a análise de dados, a apresentação dos resultados e a revisão gramatical; Daniele Caroline Hörz Engel realizou o experimento, a revisão bibliográfica, a revisão ortográfica e a apresentação dos resultados. Fontes de financiamento: Não houve fonte de financiamento. Conflito de inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 14 publications
(18 reference statements)
2
12
0
Order By: Relevance
“…Klein et al (2012) identified Andropogon bicornis L. (Poaceae) as a hibernacle of a series of stink bugs in off-season of rice crop. The same situation was observed by Pasini et al (2018), who also observed the occurrence of T. limbativentris in Andropogon lateralis (Poaceae).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Klein et al (2012) identified Andropogon bicornis L. (Poaceae) as a hibernacle of a series of stink bugs in off-season of rice crop. The same situation was observed by Pasini et al (2018), who also observed the occurrence of T. limbativentris in Andropogon lateralis (Poaceae).…”
Section: Discussionsupporting
confidence: 81%
“…Thus, its occupation was only for survival during the crop off-season. The same situation was observed in A. bicornis (Klein et al 2012, Pasini et al 2018, Engel et al 2018).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations